Penerapan Akuntansi Manajemen Lingkungan Dalam Proses Pengolahan Limbah Pada Rumah Sakit Jiwa Provinsi Jawa Barat - Anna Refiyani; Sugih Sutrisno Putra (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This research aims to provide recommendations for recording and reporting environmental physicalandmonetaryinformationthatcanbeappliedtotheMentalHospitalofWestJavaProvince. The type of research is descriptive qualitative research with a case study approach through the process of interviews, observation, and documentation. The types of data used are subject data and documentary data, the data sources are primary data and secondary data. The data analysis technique used the approach ofMiles and Huberman (1984). The results ofthis study are the Mental Hospital of West Jawa Province has carried out waste treatment properly. The treatment of environmental monetary information through the stages of identification, recognition, measurement, presentation, disclosure. This research provides recommendations for environmental cost report by using Hansen & Mowen approach. In the recommendations for physical information conducted by designing formats and completing reports that have been carried out by the hospital.